دور تحفيز الموارد البشرية في تحسين الرضا الوظيفي - شليحة, منور (My University, 2020)
The main objective of this research is to study the incentive system and its role in achieving job satisfaction for human resources in the Algerian public economic establishment. As the laser analyzes the individual one of the most important actors that contribute to achieving the goals of the institution and advancing them. The most important results of the study were represented in the following elements: There is a statistically significant correlation between the incentive system and job satisfaction in the institution under study. The monkey’s satisfaction and raising its morale is one of the most important pillars of providing job stability that helps it to perform its work efficiently and with the utmost effort to provide the institution under study with a set of material incentives, including wages, overtime rewards, and social assumptions, which in turn affect the job satisfaction of the human resource. As for the moral incentives, they are represented in the encouragement and praise of workers and have little effect on job satisfaction of human resources. The study recommended work to reconsider the incentives and wages system in line with the aspirations of human resources in order to achieve job satisfaction among workers and then increase their tastes and contribute to achieving the goals of the institution.
Keywords: motivation ، incentive system ، job satisfaction ، human resource، economic institution